Answer:
Step-by-step explanation:
Answer:
3.7 mL
Step-by-step explanation:
Answer:
(x + 3)(3x - 4)
Step-by-step explanation:
Given
3x² + 5x - 12
Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term.
product = 3 × - 12 = - 36 and sum = + 5
The factors are + 9 and - 4
Use these factors to split the x- term
3x² + 9x - 4x - 12 ( factor first/second and third/fourth terms )
= 3x(x + 3) - 4(x + 3) ← factor out (x + 3) from each term
= (x + 3)(3x - 4)
Thus
3x² + 5x - 12 = (x + 3)(3x - 4) ← in factored form
Answer:
the total cost would be $45.2
Answer:
q = 18 ?
Step-by-step explanation:
This is not a complete question but ill give it a shot!
If we are following a pattern then we see q is 11 more than r.
So we do 11 + r (7) to get 18!
mark as brainliest